Cytomegalovirus Has No Impact on Immune Thrombocytopenia Bleeding Scale or Prognostic Outcomes in Egyptian Pediatric Immune Thrombocytopenia - Mokhtar, Galila; Ragab, Iman; Bakr, Salwa; Afifi, Ahmed (Journal of Pediatric Infectious Diseases, 2019)
Background Cytomegalovirus (CMV) has been implicated as one of the etiological factors of immune thrombocytopenia (ITP) in many reports.Objectives We aimed to estimate the frequency of CMV positivity among childhood ITP patients, and to assess its impact on severity of bleeding, chronicity of the disease, and response to therapy.Methods A cross-sectional study was performed including 40 Egyptian pediatric patients with ITP. CMV infection was detected by serological testing and polymerase chain reaction (PCR). Clinical assessment for bleeding severity using ITP bleeding scale (IBLS) and initial response to therapy were included in the study.Results The prevalence of CMV DNAemia among the ITP patients was 72.5%. The virus DNAemia was higher among newly diagnosed ITP cases compared with chronic ones (85 and 60% respectively, p = 0.07). There were no significant differences in age, gender, bleeding severity, or initial clinical presentation in patients who were CMV-PCR positive or negative (p > 0.05). Refractory cases were found in 17.2% of CMV-positive cases compared with 36.4% in CMV-negative ones (p = 0.29). Specificity and sensitivity of serological assay in comparison to PCR were 72.4% and 20.69%, respectively, with a negative predictive value of 25.8%, and a positive predictive value of 66.7%.Conclusion Cytomegalovirus appears to have a high frequency among both newly diagnosed and chronic ITP patients in Egypt. CMV serological assay for IgM was not a good indicator of the presence of viral infection. CMV DNAemia seems to have no significant effect on severity of bleeding, clinical presentation, or outcomes of childhood ITP.
Keywords: thrombocytopenia; immune; cytomegalovirus; PCR